A phylogenetic perspective on P transposable element evolution in Drosophila - Clark, Jonathan B. (The National Academy of Sciences of the USA, 1997)
The P element, originally described in Drosophila melanogaster, is one of the best-studied eukaryotic transposable elements. In an attempt to understand the evolutionary dynamics of the P element family, an extensive phylogenetic analysis of 239 partial P element sequences has been completed. These sequences were obtained from 40 species in the Drosophila subgenus Sophophora. The phylogeny of the P element family is examined in the context of a phylogeny of the species in which these elements are found. An interesting feature of many of the species examined is the coexistence in the same genome of P sequences belonging to two or more divergent subfamilies. In general, P elements in Drosophila have been transmitted vertically from generation to generation over evolutionary time. However, four unequivocal cases of horizontal transfer, in which the element was transferred between species, have been identified. In addition, the P element phylogeny is best explained in numerous instances by horizontal transfer at various times in the past. These observations suggest that, as with some other transposable elements, horizontal transfer may play an important role in the maintenance of P elements in natural populations.